Experimental demonstration of quantum effects in the operation of microscopic heat engines - Klatzow, J (2018)
An account of experimental investigations into quantum effects in the operation of heat engines on the atomic scale. It consists of a description of the physical realisation of a heat engine implementation using the negative nitrogen vacancy centre in diamond. Theoretical results extending the idealised theory of quantum heat engines to account for experimental conditions are derived, along with results relating to the limit cycles of cyclic quantum heat engines. Finally the empirical existance of quantum thermodynamic signatures in the operation of microscopic heat engines are presented.